Insight into Organization of Gliadin and Glutenin Extracted from Gluten Modified by Phenolic Acids - Renata Welc-Stanowska; Konrad Kłosok; Agnieszka Nawrocka (Molecules, 2023)
The changes in the secondary structure of individual gluten protein fractions (gliadin and glutenin) caused by the supplementation of model dough with eight phenolic acids were analysed. Gliadins and glutenins were extracted from gluten samples obtained from overmixed dough. The changes in the gliadin secondary structure depended on the amount of phenolic acid added to the dough. Higher acid concentrations (0.1% and 0.2%) led to a significant reduction in the amount of α-helices and to the formation of aggregates, non-ordered secondary structures, and antiparallel β-sheets. After the addition of acids at a lower concentration (0.05%), the disaggregation of pseudo-β-sheet structures and the formation of β-turns, hydrogen-bonded β-turns, and antiparallel β-sheets were detected. In the case of glutenin, most of the phenolic acids induced the formation of intermolecular hydrogen bonds between the polypeptide chains, leading to glutenin aggregation. When phenolic acids were added at a concentration of 0.05%, the process of protein folding and regular secondary structure formation was also observed. In this system, antiparallel β-sheets and β-turns were created at the expense of pseudo-β-sheets.